On-track Measurements in Motocross: The Correlation of Neck Muscle Activity and Contact Incidents of Helmet and Neck Brace. (2016) - Thiele, Gerrit; Kafka, Patricia; Litzenberger, Stefan; Sabo, Anton
Abstract: Modern motocross racing is a very demanding and a highly injury rated sport. Within a wide range of injuries, cervical spine injuries are most feared and can even end up in different forms of paraplegia. Worn around the neck and with a non-permanent connection to rider, neck braces primarily offer a protective purpose to prevent cervical spine injuries. Beside the protective purpose, neck braces can have a supporting or a fatigue effect to the rider's neck muscles, where the effects depend on the specific neck brace design and the contact occurring between helmet and brace. Within a field test one subject was measured. During on- track measurements the contact incidents of neck brace and helmet were recorded utilizing a self-made sensor construction. The sensor construction was based on 12 electrical push-buttons and was mounted at the helmet's underside. Contact data was stored using two portable data-logging systems. Additionally muscular activity of m. sternocleidomastoideus (scm) and the upper part of trapezius (trap) were recorded while riding using a portable EMG-system. The acquired EMG data delivered information about a change of neck muscle activity while riding with the neck brace system. Activation levels and distribution of muscular activity of m. sternocleidomastoideus and m. trapezius show divergent activation levels and a changed distribution of muscular activity in response to wearing a neck brace. Related to the data of specific contact areas, it could be observed that almost one fifth of total riding time, contact between helmet and neck brace could be recorded. Low and high frequent contact areas of helmet and neck brace were calculated for total riding time, single laps and specific events, whereby a decreasing trend of contact incicdents by increasing riding time was observed. The EMG and contact data obtained delivered information about a connection of the changes of neck muscle activity and the frequent contact areas of helmet and brace. It can be concluded that driving with neck brace affects the activation levels and distribution of muscular activity of the muscles observed. According to the recent results, the correlation of contact and EMG data could be used for further neck brace design improvements and specific design adaptations to special requirements of several bike sports.